Energy consumption, CO2 emission and economic growth: Empirical evidence for Malaysia - Sarkar M.S.K.; Al-Amin A.Q.; Mustapa S.I.; Ahsan M.R. (Inderscience Publishers, 2023)
Carbon; Carbon dioxide; Economic analysis; Economic and social effects; Energy policy; Energy security; Public policy; Carbon emissions; Econometric analysis; Economic growths; Energy sustainability; Granger causality test; Green energy; Gross domestic products; Malaysia; Energy utilization